Reportagens jornalísticas rememorativas e o possível direito ao esquecimento: premissas e interfaces jurídico-comunicacionais a partir do caso Guilherme de Pádua - Dias, Luciano Souto (Universidade do Vale do Rio dos Sinos, 2021)
This study proposes to approach, by theory and empirical research, premises and legal-communicational interfaces of commemorative journalistic reports in comparison with a possible right to be forgotten, based on Guilherme de Pádua’s case. The research aims to understand how journalistic practices operate in front of a possible right to forget people who served sentences for crimes remembered in news articles. In addition, it seeks to point out clues that make it possible to understand whether journalistic references to past criminal facts that give someone a negative image in society are inherent prerogatives to freedom of expression, information, the press and the right to journalistic memory or have a stigmatizing character to the person involved. In the reported fact, capable of generating legal consequences. Furthermore, the study resorted to a discursive perspective based on pragmatic and enunciative contributions regarding the right to manifest and to memory to be exercised by victimized people, based on the crimes committed by someone who has been mentioned in reports involving past criminal facts. The content analysis methodology is adopted, which allows the investigation of selected journalistic approaches. As a result, it appears that reminiscent journalistic narratives may contain expressions that constitute excess or abuse in the exercise of freedom of expression and information and, therefore, with the potential to violate a possible right to forget the mentioned person. Finally, it is concluded that any reminiscent journalistic approaches that make reference to a person who has committed a crime must be guided by certain legal-communicational guidelines, in order to guarantee the proper exercise of journalistic practice and to avoid violating legal precepts.
Keywords: Reportagens rememorativas; Práticas jornalísticas; Comunicação; Direito ao esquecimento; Interface; Reminiscent reports; Journalistic practices; Communication; Right to be forgotten; ACCNPQ::Ciências Sociais Aplicadas::Comunicação